A robust synthesis of 7,8-didemethyl-8-hydroxy-5-deazariboflavin - Bender, Matthias; Mouritsen, Henrik; Christoffers, Jens (Beilstein Journal of Organic Chemistry, 2016)
The biosynthetic precursor of redox cofactor F420, 7,8-didemethyl-8-hydroxy-5-deazariboflavin, was prepared in four steps from 6-chlorouracil, 2-chloro-4-hydroxybenzaldehyde and bis-isopropylidene protected D-ribose. The latter aldehyde was transformed to the corresponding protected ribitylamine via the oxime, which was submitted to reduction with LiAlH4. Key advantage compared to previous syntheses is the utilization of a polyol-protective group which allowed the chromatographic purification of a key-intermediate product providing the target compound with high purity.
Keywords: carbohydrates; heterocyclic compounds; protective groups; riboflavin derivatives; ribose derivatives